Analisis Pemahaman Konsep Sains Guru Kelas Madrasah Ibtidaiyah - Wibowo, Agus Mukti (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
Most of the concepts in science are abstract ones. These concepts tend to be diffiult to study by students who have not developed formal thinking ability. This diffiulty may cause misconception, i.e. students’ conceptions which are different from those generally accepted by the scientificommunity. Understanding of teacher in non PGMI / PGSD on material science at Islamic Elementary School is still considered to be lacking or need improvement. Misconception that occurs teacher non PGMI / PGSD to learning materials science at Islamic Elementary School almost occurredin all of the material, among other things, the material of plant, animal material changes (water and solvent) light and the solar systemKeywords: material science, scientifi, misconception